Multiple Myeloma: A Paradigm for Translation of the Cancer Stem Cell Hypothesis - Agarwal, Jasmin R.; Matsui, William (Anti-Cancer Agents in Medicinal Chemistry, 2010)
Despite recent advances in drug development, multiple myeloma (MM) remains incurable for the majority of patients due to relapse and disease progression. The cancer stem cell (CSC) hypothesis may provide an explanation for these clinical findings. It suggests that the long-term proliferative potential responsible for disease initiation, maintenance, and relapse is contained within specific subpopulations of biologically distinct tumor cells. Data in MM suggest that CSCs represent a rare cell population phenotypically resembling normal memory B cells. Compared to MM plasma cells, MM CSCs also appear to be relatively resistant to a wide variety of standard anti-cancer agents suggesting they may persist following treatment and mediate tumor re-growth and relapse. A unique property CSCs share with their normal counterparts is the potential for self-renewal that likely maintains the malignant clone over time. The development of therapeutic strategies targeting the signaling elements contributing to cancer cell self-renewal has been limited primarily because the cellular processes involved are poorly understood. However, it is common that the signaling pathway components regulating normal stem cell self-renewal are aberrantly activated in human cancers and may serve as potential therapeutic targets. One class of shared regulatory pathways are those active during normal embryonic patterning and organ formation such as Hedgehog (Hh), Notch and Wingless (Wnt), and emerging data suggest that these may play a role in CSCs. Here we review the identification and characterization of MM CSCs, the role of Hh in MM, and issues to be considered during the early clinical testing of CSC targeting agents.
Keywords: Multiple myeloma